"We found the 'black spots' on campus on our own": development of inquiry skills in primary science learning with BYOD (Bring Your Own Device). Issue 2 (17th February 2016) - Song, Yanjie
ABSTRACT: This paper reports on a study situated in a one-year project "Bring Your Own Device (BYOD) for Mobile Knowledge Building, " aiming at investigating how primary school students developed their inquiry skills in science learning in BYOD-supported learning environments. Student perceptions of the BYOD-supported inquiry experience were also examined. A science learning topic of "Black Spots" in the Unit of "Safety Is Fortune" was chosen as an example of a collaborative inquiry topic appropriate for examining how students' inquiry skills are developed. Both qualitative and quantitative data were collected. A process-oriented analysis and quantitative analysis techniques were adopted to investigate students' development of inquiry skills and their perceptions of the learning experience and knowledge advancement. The research findings show that the students advanced their inquiry skills, and perceived the learning experience positively, which sheds some light on guided inquiry-based learning of science in a BYOD-supported learning environment in school education.